2023
DOI: 10.1002/smll.202205765
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Electrochemical, Photochemical, and Photoelectrochemical Reduction of CO2 to C2+ Products

Abstract: C 2+ through a single process via the CO 2 reduction reaction. Thus, this review focuses on C 2+ products generated through CO 2 ECRR, PCRR, and PECRR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 163 publications
(384 reference statements)
0
23
0
Order By: Relevance
“…There are numerous ways of transforming CO 2 to valuable products, viz., thermocatalysis, biocatalysis, , radiolysis, , and photochemical (PC), electrochemical (EC) and photoelectrochemical (PEC) techniques. The PC technique involves incorporating renewable solar energy for transforming CO 2 to produce valuable products. In contrast to the PEC process, it does not require any external potential bias and can be performed under ambient pressure and temperature conditions . The PC operation includes the absorption of CO 2 molecules at the surface of the photocatalytic composite, wherein the phenomena involving the reduction reaction of CO 2 occur in the presence of photogenerated electrons .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are numerous ways of transforming CO 2 to valuable products, viz., thermocatalysis, biocatalysis, , radiolysis, , and photochemical (PC), electrochemical (EC) and photoelectrochemical (PEC) techniques. The PC technique involves incorporating renewable solar energy for transforming CO 2 to produce valuable products. In contrast to the PEC process, it does not require any external potential bias and can be performed under ambient pressure and temperature conditions . The PC operation includes the absorption of CO 2 molecules at the surface of the photocatalytic composite, wherein the phenomena involving the reduction reaction of CO 2 occur in the presence of photogenerated electrons .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the PC technique, the PEC process involves the combined characteristics of the EC and PC techniques. Although several PEC reactor configurations have been employed, they can be classified broadly into two types . Type-I configuration consists of one metal electrode and another photoelectrode, normally a photocathode of a p-type semiconductor or a photoanode of an n-type semiconductor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…into stable chemical energy sources. [4,5] Among many reduction products of E-CO 2 RR, formate/formic acid plays an irreplaceable role in the industrial synthesis, hydrogen storage carrier, and proton exchange membrane fuel cells. [6,7] Additionally, recent studies have demonstrated that high-efficiency formate electrocatalysts can be employed as cathodes of high-safety and inexpensive aqueous Zn-CO 2 batteries.…”
Section: Introductionmentioning
confidence: 99%